Status changes in some species of Leptohyphes Eaton (Leptohyphidae, Ephemeroptera) - Molineri, Carlos (Zootaxa, 2020)
Leptohyphes Eaton is a Panamerican genus with stout nymphs inhabiting mainly mountain streams. In the present work two Leptohyphes species are revalidated: Leptohyphes comatus Allen and Leptohyphes myllonotus Allen & Roback. Additionally, a new diagnosis for the nymphal stage of Leptohyphes petersi Allen is presented, and its records from Brazil are removed.